If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6) + 2y = 90 Multiply 3 * 6 18 + 2y = 90 Solving 18 + 2y = 90 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 2y = 90 + -18 Combine like terms: 18 + -18 = 0 0 + 2y = 90 + -18 2y = 90 + -18 Combine like terms: 90 + -18 = 72 2y = 72 Divide each side by '2'. y = 36 Simplifying y = 36
| 10x-7+2x-4=9x-2+2x | | 1/4a-4=7/4-3 | | -6h=4-2h | | l^-3/4=.037 | | 5m+19-3m=-15+4m | | 8+5x=9+4x | | 3m^2/9 | | -4v-4=-6v-20 | | 3c+10=2c-3 | | 3x-60=21 | | x^-3/4=.037 | | w-7=9+5-2w | | -4y+1=1-6y-10 | | 3/8x-1/2=21/8 | | s(s/3/5)=-3/7 | | -24=5x-8x | | -6p-9=3p | | 2b+1=18 | | -7+4z=2z+7 | | y-2=-7/8(x-8) | | -7+4f=2z+7 | | -9-u=-4u | | -14+34=6x-56 | | 6x+12=-6x-17 | | Y=-3*(3*3)-1 | | 6x+12=6x-17 | | -3+7f=8f+4 | | -13+6y= | | -csc(3.14/4) | | 2sec^2=0 | | 4x+15=-9x-17 | | Y=-3*(-3*-3)-1 |